Elephant Response Unit (Eru) Dalam Upaya Penanganan Interaksi Negatif Antara Gajah Sumatra (Elephas Maximus Sumatranus) Dengan Manusia Di Sekitar Kawasan Taman Nasional Way Kambas - Paksi, Satria Icha; Fitriana, Yulia Rahma; Kuswandono, Kuswandono; Winarno, Gunardi Djoko; Febryano, Indra Gumay; Mispan, Mispan; Nazaruddin, Nazaruddin; Krismurniati, Elisabeth Devi (Universitas Pattimura, 2023)
Negative interactions between elephants and humans can cause harm to both parties, one of the efforts made is the implementation of the Elephant Response Unit (ERU) in helping to handle negative interactions between Sumatran elephants (Elephas maximus sumatranus) and humans. This study aims to determine the activities and tasks of the Elephant Response Unit (ERU) in handling negative interactions in the area around Way Kambas National Park (TNWK). Data collection was carried out by conducting observations, open interviews and collecting documentation in the form of photos of activities. The research includes direct observation of the border between forest areas and buffer villages, forest security patrols, expulsion of wild elephants and care for tame elephants. The results from direct observations show that there is no infrastructure such as canals and embankments that are evenly distributed in the area around TNWK and the lack of active participation of the community in several buffer villages in helping to handle negative interactions. Security patrol activities are in the form of tracking to identify and look for the presence of illegal activities carried out by humans in forest areas and elephant eviction patrols using tame elephants to repel wild elephants. The management of activities carried out by the Elephant Response Unit (ERU) is very important because it can help handle negative interactions between elephants and humans and safeguard forest areas.